The Influence of Innovation Culture, Work Ability and Work Commitment on Productive Behavior with Job Satisfaction as Intervening Variable: Pengaruh Budaya Inovasi, Kemampuan Kerja dan Komitmen Kerja terhadap Perilaku Produktif dengan Kepuasan Kerja sebagai Variabel Intervening - Srirahayu, Elvi; Abadiyah, Rifdah (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to determine the Influence of Innovation Culture, Work Ability and Work Commitment on Productive Behavior with Job Satisfaction as an Intervening Variable in Trenggalek Banana Chips IKM. The population used was all 100 employees of Trenggalek Banana Chips IKM, and in this study 100 people were used as samples. The sampling technique used in this study was a saturated sample. Data was collected through the distribution of questionnaires. To test the hypothesis used multiple correlation coefficient (R), determinant coefficient (R2), classical assumption test, F test and t test with the help of SPSS (Statistical Program for Social Science) version 18.0. The primary data in this study were obtained from a questionnaire whose measurement was using a Likert scale which was tested for validity and reliability. The results of this study prove that the culture of innovation (X1), work ability (X2), work commitment (X3) affect the productive behavior of employees (Y). Culture of innovation (X1), work ability (X2), work commitment (X3) affect employee job satisfaction (Z). In addition, innovation culture (X1), work ability (X2), work commitment (X3) and job satisfaction (Z) have direct and indirect effects on employee productive behavior (Y).